An appetite for aggressive behavior? Female rats, too, derive reward from winning aggressive interactions - Stina Börchers; Jil Carl; Katharina Schormair; Jean-Philippe Krieger; Mohammed Asker; Christian E. Edvardsson; Elisabeth Jerlhag; Karolina P. Skibicka (Translational Psychiatry, 2023)
Abstract While aggression is an adaptive behavior mostly triggered by competition for resources, it can also in and of itself be rewarding. Based on the common notion that female rats are not aggressive, much of aggression research has been centered around males, leading to a gap in the understanding of the female aggression neurobiology. Therefore, we asked whether intact virgin female rats experience reward from an aggressive interaction and assessed aggression seeking behavior in rats of both sexes. To validate the involvement of reward signaling, we measured mesolimbic dopamine turnover and determined the necessity of dopamine signaling for expression of aggression-seeking. Together our data indicate that female rats exhibit aggressive behavior outside of maternal context, experience winning aggressive behaviors as rewarding, and do so to a similar extent as male rats and in a dopamine-dependent manner.